2020
DOI: 10.1080/14756366.2020.1748025
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic analysis of cancer cells cultivated at acidic pH reveals phospholipid fatty acids remodelling associated with transcriptional reprogramming

Abstract: Cancer cells need to modulate the biosynthesis of membrane lipids and fatty acids to adapt themselves to an accelerated rate of cell division and survive into an extracellular environment characterised by a low pH. To gain insight this crucial survival process, we investigated the lipid composition of Mel 501 melanoma cells cultured at either physiological or acidic pH and observed the remodelling of phospholipids towards longer and more unsaturated acyl chains at low pH. This modification was related to chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Of course, the above issue of acidity-mediated drug resistance still stands in the case of more targeted or smaller molecules, but for biological compounds as well, inasmuch as it appears highly conceivable that the acidic microenvironment may well hamper the affinity of a mAB for its specific epitope. Moreover, recent evidence has shown that microenvironmental pH markedly changes the lipid composition of tumor cells, thus hampering the hypothetical binding between a ligand and its receptor [69] (Table 1).…”
Section: Small Molecules Peptides and Antibody In Targeted Therapymentioning
confidence: 99%
“…Of course, the above issue of acidity-mediated drug resistance still stands in the case of more targeted or smaller molecules, but for biological compounds as well, inasmuch as it appears highly conceivable that the acidic microenvironment may well hamper the affinity of a mAB for its specific epitope. Moreover, recent evidence has shown that microenvironmental pH markedly changes the lipid composition of tumor cells, thus hampering the hypothetical binding between a ligand and its receptor [69] (Table 1).…”
Section: Small Molecules Peptides and Antibody In Targeted Therapymentioning
confidence: 99%
“…This situation is typical when phospholipids are analyzed. Usually, an untargeted or targeted metabolomic method allows the identification of the head group, the sum of fatty acids bound to the polar portion of the molecule, and their unsaturation (i.e., PC aa C34:1 represents a phosphatidylcholine bound with two ester linkage to two fatty acids whose sum of carbons is 34 and one of them has 1 unsaturation) 6–9 . However, to identify the fatty acids bound and their position ( sn‐1 or sn‐2 ) to the phosphatidylcholine moiety, a more detailed tandem MS analysis may be required 10 …”
Section: Targeted and Untargeted Approaches For Metabolomicsmentioning
confidence: 99%
“…If it is necessary to quantify more than 50 metabolites, it is worth evaluating the cost-benefit of purchasing all the standards and the amount of bound with two ester linkage to two fatty acids whose sum of carbons is 34 and one of them has 1 unsaturation). [6][7][8][9] However, to identify the fatty acids bound and their position (sn-1 or sn-2) to the phosphatidylcholine moiety, a more detailed tandem MS analysis may be required. 10…”
Section: General Aspects Of Metabolomic Analysesmentioning
confidence: 99%
“…Genome-wide significant QTLs for FA traits in an F2 intercross between Landrace. Pig chromosome, 2 number of significant SNPs at the genome-wide level, 3 range of N snp ,4 genome map position on the Sus scrofa 11.1 genome assembly,5 nominal p-values computed using the GEMMA package,6 percentage of phenotypic variance explained by the top SNPs.…”
mentioning
confidence: 99%
“…Physical map position of SNP markers in the 749.1 kb critical region in SSC12; 2 reference allele;3 LD correlation between the key SNP marker (shaded with grey color; the SNP at 12:54956054) and corresponding SNP marker; 4 regression coefficients computed from single-marker analysis; 5 p-values computed from single-marker analysis;6 Regression coefficients calculated from conditional analysis; 7 p-values calculated from conditional analysis; bold characters represent SNP markers showing extremely high LD correlation with the key SNP marker. † Absence of regression coefficients and significance due to collinearity originated from extremely high LD with the key SNP marker.…”
mentioning
confidence: 99%